Realizing a Globally Competitive Campus: Centralized Procurement Policy for Digital Infrastructure UIN Siber Syekh Nurjati Cirebon - Suryaningsih, Nining (AMUYA: JOURNAL OF MANAGEMENT, 2025)
This policy paper examines the urgency of transforming the digital infrastructure procurement model at UIN Siber Syekh Nurjati Cirebon as a strategic step towards realizing the vision of a globally competitive campus. The current fragmented and decentralized procurement system across each work unit has created various serious challenges, including budget inefficiency, lack of technology standardization, increased cybersecurity risks, and obstacles to system integration. This situation significantly slows the pace of campus digitalization and hinders the achievement of institutional goals. Through a comprehensive analysis of existing problems, this draft proposes a centralized procurement policy as a fundamental solution. Recommendations include the formation of an integrated procurement team, the development of a technology master plan, the implementation of an e-procurement system, and the strengthening of human resource capacity. This policy aims to optimize budget utilization, ensure technological consistency and interoperability, strengthen cyber defenses, and accelerate the innovation process. Implementing this policy will not only address the weaknesses of the existing system but also build a solid, integrated, and sustainable foundation for the university's entire digital ecosystem. The results are expected to improve the effectiveness of academic and administrative services, support global collaboration, and strengthen UIN Siber Syekh Nurjati Cirebon's position as a modern and superior cyber campus.